Impact of Macro Economic Factors and Financial Development on Energy Projects - Case in ASEAN Countries - Hanh Hoang Thanh; Huy Dinh Tran Ngoc; Phuong Nguyen Thi Thanh; Nga Le Thi Viet; Anh Pham Tuan (Management, 2020)
ASEAN (The Association of SouthEast Asian Nations) demand on energy is depending on economic growth of each country, resources, and political and regulations of each country. This study aims to investigate the role of international trade, financial development, foreign direct investment (FDI) on the consumption of renewable energy (RE) in ASEAN countries of the world. The findings explore that positive nexus among the international trade, real output, financial development, foreign direct investment and consumption of RE. Last but not least, this paper will propose several recommendations and policy suggestion for ASEAN countries to manage and encourage better renewable energy projects in the region. One of its original value is that, in the globalization and integration era, environment pollution will affect all ASEAN countries and in the region, so these nations need to link together to implement renewable projects for environment pr otection and for further generation.